How do clients with multiple problems and (in)formal caretakers coproduce integrated care and support? A longitudinal study on integrated care trajectories of clients with multiple problems - Lieke Reinhoudt‐den Boer; Jeroen vanWijngaarden; Robbert Huijsman (Wiley, 2023)
Abstract Introduction Integrated care can create several advantages, such as better quality of care and better outcomes. These advantages apply especially to clients with multiple problems (CWMPs) who have multiple, interconnected needs that span health and social issues and require different health care (e.g., mental health care or addiction care), social care (e.g., social benefits) and welfare services at the same time. Integrated care is most often studied as a phenomenon taking place at the system, organizational, professional and clinical levels. Therefore, in many studies, clients seem to be implicitly conceptualized as passive recipients of care. Less research has been conducted on how clients and (in)formal caretakers coproduce integrated care. Methods We performed a longitudinal study to investigate how CWPMs and (in)formal caretakers coproduce integrated care. Data were collected among CWMPs and their (in)formal caretakers in Rotterdam, the Netherlands. CWMPs' care trajectories were followed for 1-1.5 years. CWMPs were interviewed three times at an interval of 6 months (T0, T1, T2). Informal caretakers were interviewed three times (T0, T1, T2), and formal caretakers of 16 clients were interviewed twice (T1, T2). Data in the municipal record systems about participating CWMPs were also included. Results Our study shows that the CWMPs' multidimensional needs, which should function as the organizing principle of integrated care, are rarely completely assessed at the start (first 6 weeks) of CWMPs' care trajectories. Important drivers behind this shortcoming are the urgent problems CWMPs enter the support trajectory with, their lack of trust in 'the government' and the complexity of their situations. We subsequently found two distinct types of cases. The highest level of integrated care is achieved when formal caretakers initiate an iterative process in which the CWMP's multidimensional needs are constantly further mapped out and interventions are attuned to this new information. Conclusions Our study indicates that integrated care is the joint product of formal caretakers and CWMPs. Integrated care however does not come naturally when CWMPs are 'put at the center'. Professionals need to play a leading role in engaging CWMPs to coproduce integrated care. Patient Contribution CWMPs and their (in)formal caretakers participated in this study via interviews and contributed with their experiences of the process.